DETERMINATION OF ORGANIC ACIDS, SUGARS, AND MACRO-MICRO NUTRIENT CONTENTS OF MUST IN SOME GRAPE (Vitis vinifera L.) CULTIVARS - R. I. G. Sensoy (Journal of Animal and Plant Sciences, 2015)
Effects of organic acids found in fruits on human health have been appreciated by both researchers and consumers in recent years. Sugar, macro and micro nutrient contents are also traits exposing taste and nutritional value. This study was carried out to determine the organic acids, sugars, macro-micro nutrient contents in grape must of some grape cultivars (Vitis vinifera L. cv. Silfoni, cv. Agin Beyazi, cv. Kis Kirmizisi, cv. Okuzgozu and cv. Ercis Uzumu) grown in Van province of Turkey. The organic acid values (citric, tartaric, malic, succinic, lactic, fumaric and acetic acids) varied a lot in the cultivars. The highest individual organic acid value (24.33 g tartaric acid l-1) was determined in cv. Agin Beyazi. There was no detected sucrose in the grape cultivars, but the highest amount of fructose and glucose (17.947 g 100 ml-1 and 16.670 g 100 ml-1, respectively) were determined in cv. Silfoni. There was generally a variance in macro and micro nutrient contents in the cultivars, but cv. Kis Kirmizi had the highest micronutrients except manganese.
Keywords: Grape; Macro and micro nutrients; Organic acids; Sugar